THE IMPACT OF CELEBRITY ENDORSEMENT TO YOUTH CONSUMER PURCHASE DECISION ON ADIDAS APPAREL PRODUCT - Lombo, Victor Eko Prasetyo; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2014)
Celebrity endorsements are commonly used strategies for promoting various types of products, services or brands. The main purpose of using celebrity endorser is to influence consumer behaviour, especially purchase intention that will lead to consumer purchase decision, which is directly linked to the revenue of the company. This research is conduct in Manado, North Sulawesi. The objectives of this research are to know the influence of celebrity endorsement to consumers’ purchase decision of Adidas product in Manado partially and simultaneously. This research is the causal type of research where it will investigate the influence of celebrity’s credibility on consumer purchase decision. The population in this study is the youth consumers of Adidas apparel products, whereas samples taken are 100 respondents. The conclusion of this research, there is a significant influence of attractiveness, trustworthiness, and expertise of celebrity endorser, simultaneously, on youth consumer purchase decision. There are also significant influences of attractiveness and expertise of celebrity endorser, partially, on youth consumer purchase decision. This study reveals that attractiveness is the most significant credibility source to influence youth consumer purchase decision. This means youth consumers significantly influenced by the physical appearance of celebrity endorsement in making purchase decision. Keywords: consumer purchase decision, celebrity endorsement, attractiveness